Avibacterium paragallinarum: an emerging birds pathogen in Qinling wildlife conservation center, China - Honglin Xie; Hui Li; Chenfei Yu; Yongqiang Miao; Yaping Wu; Ruoyi Jia; Qiang Zhang; Guanglin Pan; Qingyi Ma; Kangsheng Jia; Xinglong Wang (BMC, 2023)
Abstract The bacterium Avibacterium paragallinarum, previously known as Haemophilus paragallinarum, is responsible for causing infectious coryza (IC) in chickens and other avian species. In this case report, an outbreak of Avibacterium paragallinarum occurred in the Qinling area of China, resulting in clinical symptoms of facial swelling in several bird species, including Golden pheasant, Temminck's tragopan, and Peafowls, and three Golden pheasants died due to prolonged infection. Specific PCR results confirmed the presence of the pathogen in the infected birds. The report describes the clinical symptoms and pathological changes observed in the affected birds, as well as the isolation and identification of Avibacterium paragallinarum. Whole-genome sequencing and phylogenetic analysis were performed, and this is the first report of inter- and intra-species transmission of infectious coryza among wild birds in China.